Macroeconomics - Dornbusch, Rudiger, Fischer, Stanley and Startz, Richard (New Delhi, 2010)
Dornbusch, Fischer and Startz has been a long-standing, leading intermediate macroeconomic theory text since its introduction in 1978. This revision retains most of the text$1 (Bs traditional features, including a middle-of-the-road approach and very current research, while updating and simplifying the exposition. This revision focuses on making the text even easier to teach rom.s
Keywords: Economics